Association of disease‐specific causes of visual impairment and 10‐year mortality amongst Indigenous Australians: the Central Australian Ocular Health Study. (20th July 2017) - Estevez, José; Kaidonis, Georgia; Henderson, Tim; Craig, Jamie E; Landers, John
Abstract: Importance: Visual impairment significantly impairs the length and quality of life, but little is known of its impact in Indigenous Australians. Background: To investigate the association of disease‐specific causes of visual impairment with all‐cause mortality. Design: A retrospective cohort analysis. Participants: A total of 1347 Indigenous Australians aged over 40 years. Methods: Participants visiting remote medical clinics underwent clinical examinations including visual acuity, subjective refraction and slit‐lamp examination of the anterior and posterior segments. The major ocular cause of visual impairment was determined. Patients were assessed periodically in these remote clinics for the succeeding 10 years after recruitment. Mortality rates were obtained from relevant departments. Main Outcome Measures: All‐cause 10‐year mortality and its association with disease‐specific causes of visual impairment. Results: The all‐cause mortality rate for the entire cohort was 29.3% at the 10‐year completion of follow‐up. Of those with visual impairment, the overall mortality rate was 44.9%. The mortality rates differed for those with visual impairment due to cataract (59.8%), diabetic retinopathy (48.4%), trachoma (46.6%), 'other' (36.2%) and refractive error (33.4%) ( P  < 0.0001). Only those with visual impairment from diabetic retinopathy were any more likely to die during the 10 years of follow‐up when compared with those without visual impairment (HR 1.70; 95% CI, 1.00–2.87; P  = 0.049). Conclusions and Relevance: Visual impairment was associated with all‐cause mortality in a cohort of Indigenous Australians. However, diabetic retinopathy was the only ocular disease that significantly increased the risk of mortality. Visual impairment secondary to diabetic retinopathy may be an important predictor of mortality.